X - Grafton, Sue (New York : Published by G.P. Putnam's Sons, an imprint of Penguin Random House, 2015)
Sue Grafton's latest novel features a remorseless serial killer who leaves no trace of his crimes. The test is whether Kinsey can prove her case against him before she becomes his next victim.
"A Marian Wood book."
Keywords: Millhone, Kinsey (Fictitious character) -- Fiction; Women private investigators -- California -- Fiction; Serial murder investigation -- Fiction